Single and combined BTK and PI3Kδ inhibition with acalabrutinib and ACP‐319 in pre‐clinical models of aggressive lymphomas. (29th July 2019) - Spriano, Filippo; Tarantelli, Chiara; Gaudio, Eugenio; Gerlach, Magdalena M.; Priebe, Valdemar; Cascione, Luciano; Bernasconi, Elena; Targa, Altea; Mascia, Michele; Dirnhofer, Stefan; Stathis, Anastasios; Zucca, Emanuele; et al.
Summary: The B‐cell receptor and the phosphatidylinositol 3‐kinase (PI3K) signalling pathways, together with their downstream partners, represent important therapeutic targets for B‐cell lymphomas. Here, we evaluated the activity of acalabrutinib (ACP‐196) and ACP‐319 (AMG‐319), second generation inhibitors of Bruton tyrosine kinase (BTK) and PI3Kδ inhibitor, respectively, in lymphoma pre‐clinical models. The two compounds showed activity in activated B‐cell‐like diffuse large B‐cell lymphoma (ABC DLBCL), mantle cell lymphoma and marginal zone lymphoma. Two in vivo experiments with ABC DLBCL and MCL xenografts confirmed the effect of the single agents. Benefit was achieved by exposing the lymphoma cell lines to both acalabrutinib and ACP‐319. Two cell lines presented a discordant response to first and second generation BTK inhibitors, probably due to the inhibition by ibrutinib of kinases other than BTK. In conclusion, our data sustain the on‐going current trials with acalabrutinib and ACP‐319 as single agents and provide the basis for the investigation of their combination as well.